ACUTE AND CHRONIC GASTRITIS AND GASTRODUODENITIS IN CHILDREN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Nowadays, among children, chronic gastritis and gastroduodenitis, as well as peptic ulcer disease of the stomach and duodenum, constitute a major part of gastrointestinal disorders. Therefore, having sufficient knowledge about these diseases, taking timely preventive measures, and starting treatment early make it possible to control these conditions completely and avoid potential complications. This article describes the causes, clinical presentation, treatment, and prevention of chronic gastritis and gastroduodenitis, and peptic ulcer disease of the stomach and duodenum.